Der Rettungsanker am Unfallort: Erste Erkenntnisse einer qualitativen Studie über das Erleben kollegialer Erstbetreuung nach potenziell traumatisierenden Ereignissen - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)
Objectives: Health care experts recommend prompt low-threshold psychosocial assistance for employees who have experienced a potentially traumatic event. Collegial first response constitutes such a form of acute care: colleagues of those involved in the accident come straight to the scene, where it is their job to look after the employees concerned. How this is viewed by the people involved has been unclear until now. The objective, therefore, was to gather initial findings about the experience of collegial first response within the context of a potentially traumatic event. Methods: As part of a prospective cohort study, 22 drivers at a German transport company were asked in guideline-based interviews about their experience of suffering an accident at work and the care provided at the scene of the accident. The material collected was assessed with the help of a structured content analysis based on Mayring and a classification system designed to be deductive/inductive. Findings: The experience of the accident could be broken down into four consecutive periods of time: the moment of the accident, the ensuing interval, the time spent dealing with the damage and the departure from the scene of the accident. During this time the people affected felt helpless and overwhelmed at first. They then looked for something that could give them security and guidance. The arrival of a collegial peer supporter at the scene of the accident came as a great relief to the people concerned. The peer supporter was perceived as someone who could give them a sense of no longer being alone at the scene of the accident, of being cared for and receiving assistance. Conclusions: The experience of an accident cannot be reduced down to the moment in which it suddenly occurs. In fact, for those affected it continues until leaving the scene of the accident and beyond. Their state of health at this time cannot typically be described as stable. Collegial first response plays a vital role in the system of assistance deployed at the scene of the accident from the perspective of the people involved.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Accident; Collegial peer support; Psychological first aid; Research in medical care; Transport; Trauma

Psychische Traumatisierung im Fahrdienst: Über die Bedeutung der zeitnahen Versorgung nach traumatischen Ereignissen - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Gesundheitswesen, 2015)

Sickness absence among peer-supported drivers after occupational trauma - Clarner, Annika; Uter, Wolfgang; Ruhmann, L.; Wrenger, Nina; Martin, A.; Drexler, Hans (Occupational Medicine-Oxford, 2017)
Psychological first aid is a common approach for providing support after potentially traumatic events (PTEs). In Germany, a peer support model is recommended by the German Statutory Accident Insurance (DGUV) to reduce sickness absence after occupational accidents, especially in public transportation. However, data on the effectiveness of peer support are very sparse.To analyse whether peer support has an impact on sickness absence after work-related traumatic events in public transportation.An analysis was conducted in two German public transportation corporations. Due to ethical requirements, we used a historical cohort study comparing peer support by colleagues (VAG-1), peer support at supervisor level (VGF) and a non-intervention group (VAG-0). The study period was from March 2003 to December 2012. We used a negative binominal regression model to estimate the relative risk associated with the interventions and potential confounders.A total of 259 incident PTEs in employees were observed. A regression analysis identified the severity of PTE (severe and fatal events), VGF and age as significant factors in predicting duration of post-event sickness absence. In a stratified analysis, the mode of peer support (VGF) and age predicted sickness absence for less severe PTEs but this was not significant for severe PTEs.Severe and fatal PTEs had the strongest impact on sickness absence after PTEs. For less severe PTE, peer support provided by colleagues may be superior to supervisor support.
EVALuna2:9760

The Lifeline at the Scene of an Accident - Wrenger, Nina; Staples, Ronald; Grässel, Elmar; Drexler, Hans; Clarner, Annika (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2015)

"Und wann kümmern wir uns um den Fahrer?" - Erstbetreuung als Teil der Versorgung bei drohender psychischer Traumatisierung im Fahrdienst: Bedeutung für die arbeitsmedizinische Versorgungspraxis - Clarner, Annika; Wrenger, Nina; Voss, Amanda Sophie; Uter, Wolfgang; Martin, A.; Drexler, Hans (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
Background and objective: Events causing fatalities and serious damage occur in the railway, transportation and regional public transport (OPNV) sector every year. From the perspective of occupational medicine, it is essential to provide adequate care for drivers who are potentially at risk of psychological trauma. A widespread concept of provision is first-response systems in the form of layman- based acute care after accidents at work involving drivers (VBG [German accident insurance provider]). The objective of this paper was a scientific evaluation of these systems. Methodology: Two retrospective cohort studies were conducted with regard to factors influencing length of absence and illness progression among drivers working for two German transport companies in Bavaria and Hesse. Whilst the first study investigated factors influencing post-traumatic stress following first response care, the second cohort study examined the efficacy associated with different forms of first response (collegial, hierarchical or none). The study covered accidents at work between 2003 and 2013. Results: The pilot study covered 59 first response deployments. It was possible to analyse the progression of 259 cases of illness among drivers within the scope of the main study. Accidents in which the casualties were seriously or fatally injured constituted the strongest predictor for drivers. Differences relating to response systems were found in terms of the length of absences when slight damage occurred. There was clear evidence in the control group of an insignificant trend towards a reduction in periods of absence and a significantly low score for the development of post-traumatic stress. Conclusions: When it comes to the form of acute care provision, peer-based systems with an eye to periods of absence may be classed as worth recommending in the case of events causing less serious damage. On the other hand, it is not possible to infer a switchover to the English guideline (NICE) in the sense of "watchful waiting" without first response for Germany in future. The severity of injury is the biggest factor in post-traumatic stress after traumatic events in driving jobs and necessitates binding regulations for damaging events of this kind and accompanying research in the field of occupational medical care.
CRIS-Team Scopus Importer:2020-05-11
Keywords: Accident; Incapacity for work or PTSD; Traffic; Transport; Trauma